ANALISIS IMPLEMENTASI PROGRAM TAHFIDZ DI SDT AL-MUHIBBIIN BETUNG - Natasyah Ifah Faridhona; Muhamad Afandi; Miftahul Husni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of the Qur’an memorization (tahfidz) program as a means of fostering students’ religious character and increasing their love for the Qur’an from an early age. SDT Al-Muhibbiin Betung Banyuasin is one of the elementary schools that implements the Qur’an memorization program as a flagship program in learning activities. However, several obstacles are still found in its implementation, such as decreasing student motivation in memorizing, difficulties in memorizing certain verses, and limited variations in learning methods. Therefore, this study aims to analyze the implementation of the Qur’an memorization program at SDT Al-Muhibbiin Betung Banyuasin, including its strengths, weaknesses, opportunities, and threats. This study uses a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, tahfidz teachers, and students participating in the tahfidz program. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that the implementation of the tahfidz program at SDT Al-Muhibbiin Betung has several strengths, including competent tahfidz teachers, clear memorization targets at each grade level, and support from the school. However, there are also obstacles such as unstable student motivation, limited learning time, and the influence of external factors. Nevertheless, the tahfidz program still has opportunities to be further developed through improved learning strategies, strengthened program management, and support from all parties in the school.